Influence of Some Packages of Technology on Pests Development on Chili Plants in Highland Area - I Putu Sudiarta; Luciana Delavega; Ni Nengah Darmiati; Gusti Ngurah Alit Susanta Wirya; I Ketut Sumiartha; I Made Supartha Utama (Dwijendra University, 2019)
Chili is a type of plant that can grow in various types of area, in lowland and highland areas and also can adapt well at a temperature of 24-27 ˚C. The purpose of this research in order to know the influence and effectiveness of the packages technology of Trichoderma sp. mixed with compost, rain shelter and pesticides to control the development of pests in cayenne chili plants and long chili in the highland area. This research was conducted from September 2017 to February 2018, in Pancasari Village, Buleleng Regency, Bali. The study used a Factorial Randomized Block Design with two factors and four times replications. The first factor was chili type (cayenne chili and long chilli), and the second factor was the use of technologies, compost plus Trichoderma sp., rain shelter, and pesticide. The variable was observed in this research were population of aphis, percentage of fruit fly and yields. The results showed that all treatment technologies effectively suppressed pests development when compared with control. The result show that the damage population of the highest aphis pest was found in control about 194 of Aphids, and population of aphids on pesticide treatment were not found. The result show that damage percentage of the highest fruit fly pest was found in control treatment with the percentage of 76,55% while the lowest percentage was found in pecticide treatment. The rain shelter treatment showed the highest yields were reached 405,87 gr and the control treatment showed the lowest yields were reached 12,03 gr.